Trade in agricultural products in green and livestock markets in Republic of Srpska - Ostojić Aleksandar; Drinić Ljiljana; Mirjanić Stevo; Vaško Željko; Rokvić Gordana; Mrdalj Vesna; Figurek Aleksandra (Agroznanje, 2013)
A significant part of agricultural products in the Republic of Srpska is produced on farms. The characteristics of this production are small amounts of marketable surplus, heterogeneous assortment of uneven quality, seasonal variations in supply and the like. All this make the sale of these products to industrial processors and trade intermediaries more difficult. Therefore, a portion of agricultural products remain unsold or sold under unfavourable conditions (low cost, delayed payment). In such a situation, green and cattle markets arise as an efficient form of distribution of agricultural and other complementary products through which a successful connection between buyers and sellers can be made. The subject of this research is to analyze the agricultural products trade flows in green and livestock markets in the Republic of Srpska. The analysis include the sale of the products of plant and animal origin in the period 2007-2011. The research is based on the available data gathered through a desk research method as well as a field research method for making the study "The role and importance of green and livestock markets in the sale of agricultural products in the Republic of Srpska". Basic data have been taken from the statistical publications of the Statistical Office of the RS, which are systematized using standard mathematical and statistical methods.